The Effect Of The Organizational Development Process On The Performance Of Workers At Tishreen University (A Field Study) (Latakia University Journal - Economic and Legal Sciences Series, 2023)
This study aimed to determine the relationship between the Process of Organizational Development and the Performance of Workers at Tishreen University. The researcher relied on Both, the Deductive Approach and the Descriptive Approach. He distributed a questionnaire to (72) Workers in the Senior and Middle Administration in the presidency of Tishreen University, In addition the Senior and Middle Administration in the Colleges and Institutes affiliated to the Ministry of Higher Education and Scientific Research at the University Under Study, which (52) questionnaire were valid for use, and then a field study was conducted in order to demonstrate this relationship between the two variables. The researcher reached through the study; To the Acceptable interest of the Senior Administration at the university under study in the process of Organizational Development, and improving the performance level of its Workers. The study concluded that there is a direct positive relationship between the Organizational Development Process and the performance of Workers. Thus, There is a Significant impact of the Organizational Development Process on the Performance of Workers at Tishreen University; This study also reached a set of Recommendations and Suggestions, which would contribute positively to enhancing the Impact of the Organizational Development Process on the Performance of Workers at the University Under Study.